An almost-too-late warning mechanism for currency crises - Jesus Crespo Cuaresma; Tomas Slacik (University of Innsbruck, Department of Public Finance, 2007)
We propose exploiting the term structure of relative interest rates to obtain estimates of changes in the timing of a currency crisis as perceived by market participants. Our indicator can be used to evaluate the relative probability of a crisis occurring in one week as compared to a crisis happening after one week but in less than a month. We give empirical evidence that the indicator performs well for two important currency crises in Eastern Europe: the crisis in the Czech Republic in 1997 and the Russian crisis in 1998.
Keywords: F31; F34; E43; 330; currency crisis; term structure of interest rates; transition economies; Währungskrise; Systemtransformation; Schätzung; Transformationsstaaten; Osteuropa